RETRACTED: Study on the design of composite beams under complex environment in mountainous areas - Zhao, Yicheng; Sun, Caizhi; Li, Sheng (Frontiers in Earth Science, 2023)
The mountain area is faced with complex conditions such as vertical and horizontal valleys, complex geological topography, many earthquake fault zones, high seismic intensity, fragile ecology, and changeable climate. The traditional concrete bridges have heavy weight, high consumption of sand and gravel materials, large structural dimensions of steel box composite bridges, high steel consumption and poor overall horizontal performance of steel plate composite beams, which are not suitable for mountain construction conditions. Therefore, based on the construction environment and application requirements of highway bridges in mountainous areas, the structural scheme of steel box-steel plate composite beam is put forward in this paper, and the design of a 25 m ~ 50 m standard span steel box-steel plate composite beam is studied. The results show that the steel box-steel plate composite beam structure scheme is adopted, which has excellent stiffness characteristics of steel box girder and simple structure of steel plate girder. It has the mechanical characteristics of "balanced transverse force and excellent longitudinal force", so it is a reasonable choice for small radius curved beam bridge in a mountainous area, so it is a reasonable choice for small radius curved beam bridge in a mountainous area. The steel box-steel plate composite beam adopts the integrated technology of manufacture, transportation and installation, which can better meet the road transport conditions in the mountain area. The longitudinal assembly of the manufacturing unit as the installation unit can ensure the rapid and high-precision installation of the construction site, and the assembly construction of the bridge in the mountain area has been realized. The technical and economic comparison shows that the mechanical performance of steel box-steel plate composite beam is similar to that of steel box beam and obviously better than that of steel plate girder. The steel consumption and construction period of steel box-steel plate composite beam are similar to that of steel plate girder, and is significantly less than that of steel box girder. Therefore, the steel box-steel plate composite beam is a good choice for mountain bridge construction.